Assessing the impact of public safety leader development in Australasia - Herrington, Victoria (Policing and society, 2017)
Public safety organisations across the world invest a great deal of time and money in developing their leaders. It is perhaps surprising, then, that there is relatively little literature assessing the impact that such development opportunities have. This paper serves to address this gap by examining one such leader development programme in Australia. Seventy participants were followed for one year, and statistically significant shifts in self-reported leadership behaviour were identified. Interviews with an additional 30 former students suggested that such behavioural changes were preserved over the longer term, and may compound as individuals utilise both their formal learning and on the job experience to enhance their leadership effectiveness. This suggests that for a relatively modest upfront investment in human capital, considerable organisational gains are possible. The extent to which such gains are measurable or can be characterised in monetary terms is discussed, ahead of a conclusion that sets out an agenda for future research to better understand how leadership and its development are conceptualised, operationalised, and realised in public safety agencies.